La clonación humana (1997)
The recent clonation experiment of a sheep carried out by Dr Wilmut, at Roslin Institute, has caused astonishment and fear because it can be extrapolated to man. This article studies antecedent to the clonation experiments which were carried out at the beginning of the 90s. It also describes in detail the technique used by the Scottish scientist, and examines the ethical implications of its generalized use in animal husbandry, lab animals and human beings. Only the second use seems morally justifiable.